2020
DOI: 10.17784/mtprehabjournal.2017.15.453
|View full text |Cite
|
Sign up to set email alerts
|

Measurement reliability of endotracheal tubes cuff pressure between industrial and handmade devices

Abstract: Introduction:The cuff pressure is measured in industrial equipment, however, be valid in the craft equipment is still questioned. Objective: To evaluate the reliability of the measurement methods of cuff pressure endotracheal tubes with industrialized and handmade equipment. Method: Were analyzed 40 endotracheal tubes, two brands (Solidor  and Ruschelit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It is suggested that Cuff pressure should be maintained between 25 and 34 cm H2O. Gastric content aspiration is securely prevented at pressures above 25 cm H2O, whereas broncho-aspiration is possible at pressures below 20 cm H2O 10 . In this study insignificant difference was found between the groups with cuff pressure at baseline of the patients (p =0.25) and mean value of cuff pressure at 60 minutes in air filled cuff group patients was 42.20±9.05 cm H2O and in saline filled cuff group was 21.34±4.49 cm H2O (p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that Cuff pressure should be maintained between 25 and 34 cm H2O. Gastric content aspiration is securely prevented at pressures above 25 cm H2O, whereas broncho-aspiration is possible at pressures below 20 cm H2O 10 . In this study insignificant difference was found between the groups with cuff pressure at baseline of the patients (p =0.25) and mean value of cuff pressure at 60 minutes in air filled cuff group patients was 42.20±9.05 cm H2O and in saline filled cuff group was 21.34±4.49 cm H2O (p=0.001).…”
Section: Discussionmentioning
confidence: 99%